2011
DOI: 10.1016/j.bbadis.2011.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Development of diabetes in lean Ncb5or-null mice is associated with manifestations of endoplasmic reticulum and oxidative stress in beta cells

Abstract: NADH-cytochrome b5 oxidoreductase (Ncb5or) is an endoplasmic reticulum (ER)-associated redox enzyme involved in fatty acid metabolism, and phenotypic abnormalities of Ncb5or−/− mice include diabetes and lipoatrophy. These mice are lean and insulin-sensitive but become hyperglycemic at age 7 weeks as a result of β-cell dysfunction and loss. Here we examine early cellular and molecular events associated with manifestations of β-cell defects in Ncb5or−/− mice. We observe lower islet β-cell content in pancreata at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
23
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 54 publications
7
23
1
Order By: Relevance
“…Naturally occurring polymorphism’s in human NCB5OR have been shown result in increased proteasomal degradation (10). Transgenic mice globally deficient in NCB5OR (GKO) have low birth weight (beginning at 2 weeks of age), petite skeletal structure/build, impaired lipid storage and lipoatrophy, hypermetabolism, mitochondrial dysfunction, and early-onset diabetes from necrotic beta cell loss when compared to normal or wild-type (WT) control mice (1114). We recently discovered that global loss of NCB5OR results in mild to moderate anemia, significant changes in iron related pathways, and iron deficiency in iron rich tissues such as the spleen and liver (15).…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring polymorphism’s in human NCB5OR have been shown result in increased proteasomal degradation (10). Transgenic mice globally deficient in NCB5OR (GKO) have low birth weight (beginning at 2 weeks of age), petite skeletal structure/build, impaired lipid storage and lipoatrophy, hypermetabolism, mitochondrial dysfunction, and early-onset diabetes from necrotic beta cell loss when compared to normal or wild-type (WT) control mice (1114). We recently discovered that global loss of NCB5OR results in mild to moderate anemia, significant changes in iron related pathways, and iron deficiency in iron rich tissues such as the spleen and liver (15).…”
Section: Introductionmentioning
confidence: 99%
“…Although the molecular and cellular mechanisms underlying FFA-induced ␤-cell apoptosis are not fully understood, participating processes include generation of reactive oxygen species (ROS) and mitochondrial dysfunction (8 -11), production of ceramide and nitric oxide (NO) (4,12), and induction of endoplasmic reticulum stress (13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Prediabetic Ncb5or −/− mice exhibit β‐cell dysfunction manifest by reduced islet insulin content, impaired glucose‐stimulated insulin secretion, and glucose intolerance 11. We have recently demonstrated that Ncb5or −/− β‐cell defects include increased intracellular free SFA levels and manifestations of ER and oxidative stress and that progression of ER distention correlates with the magnitude of β‐cell dysfunction and loss in prediabetic Ncb5or −/− mice 16.…”
Section: Introductionmentioning
confidence: 91%